FRAMING ANALYSIS OF THE NEWS KOMODO 'JURRASIC PARK' PROJECT ON LIPUTAN6.COM AND TEMPO.CO - Saifuddin Zuhri; Abdhi Gusti Illahi; Devi Aprilliana (JOSAR (Journal of Students Academic Research), 2021)
This study aims to obtain an overview and analyze an understanding of the way Liputan6.com and Tempo.co frame reporting on the Komodo 'Jurassic Park' Project. This is related to the virality of a photo of a Komodo dragon blocking a project truck. Currently, in the three areas of Komodo National Park, two different investors are currently building tourist facilities. This development stems from President Jokowi's dream of making Komodo National Park and Labuan Bajo as premium tourism. The framing analysis model that used in this study belongs to Zhongdang Pan and Gerald M. Kosicky. The results obtained from this study are the similarities of journalists in writing facts. Both Tempo.co and Liputan6.com highlighted statements from government people (who were involved in this project). Liputan6.com also includes public opinion on twitter against this project while Tempo.co positions that this project does not harm the community or Komodo because the government pays attention to environmental, social and cultural aspects.